1991
DOI: 10.1007/bf00635632
|View full text |Cite
|
Sign up to set email alerts
|

The role of anaerobic ability in middle distance running performance

Abstract: The purpose of this study was to assess the relationship between anaerobic ability and middle distance running performance. Ten runners of similar performance capacities (5 km times: 16.72, SE 0.2 min) were examined during 4 weeks of controlled training. The runners performed a battery of tests each week [maximum oxygen consumption (VO2max), vertical jump, and Margaria power run] and raced 5 km three times (weeks 1, 2, 4) on an indoor 200-m track (all subjects competing). Regression analysis revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 13 publications
0
31
0
1
Order By: Relevance
“…Furthermore, they found t lim to be highly variable among the subjects (range: 262± 598 s), positively related with the lactate threshold r 0X58 and unrelated to O 2 max . These ®ndings, as well as the data of previous works which have focused on the relative importance of aerobic and anaerobic energy release during exhausting exercise of medium duration (Medbù and Tabata 1989;Houmard et al 1991;Craig et al 1993), suggested the hypothesis that although the time to exhaustion at I O 2 max has a large aerobic component it also re¯ects runners' ability to exercise anaerobically. For the reasons described above, this is particularly true when the exercise intensity associated with O 2 max is assessed during a continuous incremental test with steps of short duration.…”
Section: Introductionmentioning
confidence: 72%
“…Furthermore, they found t lim to be highly variable among the subjects (range: 262± 598 s), positively related with the lactate threshold r 0X58 and unrelated to O 2 max . These ®ndings, as well as the data of previous works which have focused on the relative importance of aerobic and anaerobic energy release during exhausting exercise of medium duration (Medbù and Tabata 1989;Houmard et al 1991;Craig et al 1993), suggested the hypothesis that although the time to exhaustion at I O 2 max has a large aerobic component it also re¯ects runners' ability to exercise anaerobically. For the reasons described above, this is particularly true when the exercise intensity associated with O 2 max is assessed during a continuous incremental test with steps of short duration.…”
Section: Introductionmentioning
confidence: 72%
“…In the present study, average VO2max was 57 ml/kg/min while in both of the two aforementioned studies of male runners average VO2max was approximately 62 ml/kg/ min. 4,6 This is not a large difference, but could perhaps partially explain the discrepancies. In the aforementioned study of female cross-country runners 5 , VO2max was actually lower (54 ml/kg/min) than that of the present study which is perplexing unless we assume that they simply had better racing ability due to better running economy (a variable not assessed in the present study).…”
Section: Gmentioning
confidence: 92%
“…Deason et al (1991) showed that in male distance runners a strong relationship existed between 800 m run time and the more purely anaerobic 300 m run time (r = 0.826) while the relationship between 800 m run time and VO2max was non-significant (r = -0.491) with alpha set at 0.05. Houmard et al 6 found in well-trained male distance runners that 5 km race time (another middle distance) was moderately correlated to both vertical jump height (r = -0.73) and VO2max (r = -0.60). In a study of NCAA Division I female cross-country runners, it was found that anaerobic energy production contributed to 5 km velocity along with aerobic contributions.…”
Section: Gmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we used a manifestation of performance (3.6 km uphill run time) instead. V VO2max has been reported as able to represent aerobic and anaerobic modes of energy production in an integrated manner 7,27 , in addition to being associated with running economy 6,28,29 . This may partly explain its superior predictive power for a short, uphill event in this study.…”
Section: Discussionmentioning
confidence: 99%